Hybrid adipose graft materials synthesized from chemically modified adipose extracellular matrix. Issue 1 (15th July 2021) - Li, Shue; Liu, Yiming; McCann, Jacob; Ravnic, Dino J.; Gimble, Jeffrey M.; Hayes, Daniel J.
Abstract: Decellularized extracellular matrix (ECM) from tissues is a promising biomaterial that can provide a complex 3D microenvironment capable of modulating cell response and tissue regeneration. In this study, we have integrated the decellularized thiolated adipose‐derived ECM, at different concentrations, with polyethylene glycol (PEG) using Michael addition between thiol and acrylate moieties. The potential for this material to support adipogenic differentiation of human adipose‐derived stem cells was evaluated by encapsulating cells in hydrogels with increasing concentrations of chemically modified ECM (mECM). Our results demonstrated a positive correlation between the ECM content in the hydrogels and cell proliferation, adipogenic marker expression, and lipid formation and accumulation. Furthermore, we have shown host cell infiltration and enhanced adipogenesis in vivo after implantation. These findings support the graft as a potential alternative for adipose tissue regeneration.